1995
DOI: 10.1152/ajpregu.1995.269.4.r787
|View full text |Cite
|
Sign up to set email alerts
|

Central inhibitory action of peptide YY on gastric motility in rats

Abstract: Specific peptide YY (PYY) binding sites have recently been identified autoradiographically in the area postrema, nucleus of the solitary tract, and dorsal motor nucleus regions [collectively referred to as the dorsal vagal complex (DVC)] in rats. These medullary brain stem regions are responsible for vagovagal reflex control of gastric function, including gastric motility. We propose that PYY can modulate gastrointestinal functions, such as gastric motility, by interacting with PYY binding sites found in DVC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 0 publications
4
46
0
Order By: Relevance
“…Findings include 1) peripherally administered PYY (1-36) binds in a saturable manner to specific areas in the DVC (23) and induces c-Fos immunoreactivity in these areas (6); 2) PYY(1-36) and NPY(3-36) (a Y 2 agonist) dose dependently inhibit excitatory postsynaptic currents in cholinergic neurons of the dorsal motor nucleus of the vagus (10); 3) injection of PYY or Y 2 agonists [NPY or PYY ] into the DVC inhibits neurons of the dorsal motor nucleus of the vagus, as well as TRH-induced gastric motility (11,12,14); 4) intracisternal injections of PYY(1-36) inhibit gastric emptying, and this inhibition is attenuated by vagotomy (13); and 5) intracerebroventricular injection of NPY(3-36) (Y 2 agonist) dose dependently delays gastric emptying of solids, as well as impairs antral contractions and antropyloric coordination in the emptying period (25). In contrast to these Y 2 receptor-dependent effects, Y 1 receptor-mediated effects on gastric emptying appear to be stimulatory.…”
Section: Discussionmentioning
confidence: 99%
“…Findings include 1) peripherally administered PYY (1-36) binds in a saturable manner to specific areas in the DVC (23) and induces c-Fos immunoreactivity in these areas (6); 2) PYY(1-36) and NPY(3-36) (a Y 2 agonist) dose dependently inhibit excitatory postsynaptic currents in cholinergic neurons of the dorsal motor nucleus of the vagus (10); 3) injection of PYY or Y 2 agonists [NPY or PYY ] into the DVC inhibits neurons of the dorsal motor nucleus of the vagus, as well as TRH-induced gastric motility (11,12,14); 4) intracisternal injections of PYY(1-36) inhibit gastric emptying, and this inhibition is attenuated by vagotomy (13); and 5) intracerebroventricular injection of NPY(3-36) (Y 2 agonist) dose dependently delays gastric emptying of solids, as well as impairs antral contractions and antropyloric coordination in the emptying period (25). In contrast to these Y 2 receptor-dependent effects, Y 1 receptor-mediated effects on gastric emptying appear to be stimulatory.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of local synaptic inputs onto DMV neurons arises from the adjacent NTS, which contains the A2 catecholaminergic group (14). With the noticeable exception of the esophageal-mediated gastric relaxation (21,28), the vast majority of vagovagal reflexes induce a powerful inhibition of the DMV firing rate via activation of inhibitory NTS neurons, which then inhibit DMV vagal output (4,7,8,10,13,16,22,28,29). An inhibitory effect on gastric tone and motility, however, can also be attained by stimulation of DMV neurons forming inhibitory nonadrenergic, noncholinergic pathways (12,28).…”
Section: Discussionmentioning
confidence: 99%
“…33 The left DVC represents a specific site of action for [Leu 31 , Pro 34 ]NPY to elicit central stimulation of bile secretion, because the peptide was ineffective when delivered to sites close to, but outside of, the left DVC and also delivered to the right DVC. In addition, the complete suppression of the bile response to [Leu 31 , Pro 34 ]NPY microinjected to the left DVC by hepatic branch vagotomy suggests that the peptide may primarily or secondarily activate preganglionic neurons contributing to vagal innervation of the liver. This finding is further supported by previous studies that indicate that microinjection of NPY or PYY into the DVC induces physiological modulations through the vagus nerve.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is further supported by previous studies that indicate that microinjection of NPY or PYY into the DVC induces physiological modulations through the vagus nerve. 13,30,34 Retrograde tracing techniques have revealed that most of the hepatic vagal preganglionic efferent neurons originate from the left DMN, and orthograde tracing has revealed a predominant pattern of hepatic vagal afferent terminations within the left NST, and some hepatic vagal nerve fibers also have projections from the nucleus ambiguus. [35][36][37] Furthermore, interconnections between the NST and the DMN allow cross-talk between the afferent and efferent loops of the vagal nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation